Postoperative rectovaginal fistula: Can colonic pull‐through delayed coloanal anastomosis avoid the need for definitive stoma? An experience of 28 consecutives cases. (6th April 2022) - Blondeau, Marc; Labiad, Camélia; Melka, Dan; de Ponthaud, Charles; Giacca, Massimo; Monsinjon, Marie; Panis, Yves
Abstract: Aim: Management of rectovaginal fistula (RVF) remains a challenge, especially in cases of postoperative RVF as they are often large and surrounded by inflammatory and fibrotic tissue, making local repair difficult or even impossible. In this situation, colonic pull‐through delayed coloanal anastomosis (DCAA) could be an interesting option. The aim of this study was to assess the results of DCAA for RVF observed after rectal surgery. Methods: All patients who underwent DCAA for RVF were reviewed. Success was defined as a patient without stoma and without any symptoms of recurrent RVF at the end of follow‐up. Results: From January 2010 to December 2020, 28 DCAA were performed for RVF after rectal surgery for rectal cancer ( n = 21) or endometriosis ( n = 7). Ten patients (36%) had at least one previous local procedure before DCAA. DCAA was associated with temporary ileostomy in 22/28 cases (79%). After a mean follow‐up of 23 ± 23 (2–82) months, the success rate was 86% (24/28): three patients (11%) required a definitive stoma because of poor functional results ( n = 1), chronic pelvic sepsis with anastomotic leakage ( n = 1) or stoma reversal refused ( n = 1). Another patient (3%) presented with recurrence of RVF, 26 months after DCAA. Although not significant, the success rate was higher in cases of DCAA with diverting stoma (20/22, 91%) than without (4/6, 67%) ( p = 0.191). Conclusion: In cases of postoperative RVF, DCAA is a safe option which can avoid definitive stoma in the great majority of the patients. Concomitant use of a temporary stoma appears to slightly increase the success rate.